Strange and Lamentable News: True Crime and Domestic Tragedy in Early Modern England - Berg, Dianne. (Tufts University. Tisch Library., 2020)
Thesis (Ph.D.)--Tufts University, 2020.; Submitted to the Dept. of English.; Advisor: Judith Haber.; Committee: Kevin Dunn, John Fyler, and Virginia Mason Vaughan.; Keywords: English literature, Gender studies, and History.